Pengaruh Pemakaian Scrubber terhadap Kadar Emisi Gas SO,, NO2, CO dan Debu pada Pembakaran Batu Kapur: The Influence of Using Scrubber to Gas Emission Contents SOy NOj, CO and Dust in Limestone Processing Industry - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Redisari and Kalisari Villages in Rowokele sub-district, Kebumen Regency, Central Java is the center of lime stone mining and processing Industry. Because of the scarcity of fire wood, the local people started to use coal. The emission of hydro carbon (HC), sulphuric dioxyde (SO2), nitrogen dioxyde (NO2), carbon monoxyde (CO), gases and dust resulted a negative impacts from coal which was feighter the local people. This research aims to find out a method for treating emitted gases of SO2, NO2, CO and dust. So it is not influential to worker public health and environtmental. The instrument for the emitted gas treatment consist of a scrubber/ absorber chimney stuffed with packing in the middle part in order to slow down the contact between the flow of gas from below with the chalk solution sprayed over the upper part of the scrubber with a plump. To keep the flow stay laminer, the instrument was equipped with an exhauser. The location from which the sample of knitted gases of SO2, NO2, CO and dust were taken from inlet (pre test) and out let (post test) with 6 times repetitions. Then, a statistic test was made using the t-test and Anava-test The results showed that the highest efficiency of decrease of emitted SO2 is 69.82%, NO2 is 79,11% and these two gases were grouped into E 20% T Lk 5% (E = Experiment, T = height of scrubber chimney, Lk = chalk solution) for the dust, the highest efficiency of decrease was 87,51%, in the group of E 25% Lk 3%. Based on the statistic test, it was obtained that the probability value (P = 0,000) which meant a significant efficiency of decrease.